Analisa Pertumbuhan Wilayah Dan Perubahan Lahan Terhadap Pengembangan Fungsi Jalan Garuda Sakti, Kecamtan Tampan, Pekanbaru - Zulhandika Zulhandika; Rian Tri Komara; Sri Djuniati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Tampan is one of the sub-districts in Pekanbaru City, with flat geographical position between 0 ° 42'-0 ° 50 'North Latitude and between 101 ° 35'-101 ° 43' East Longitude. In Regional Regulation Spatial Plan Pekanbaru, Tampan subdistrict is a Development Area (WP) V. Development Area V is a center of residential, occupation, industrial, office, government and trade. The number of residents Kecamatan Tampan are 220,208 in 2015. This increased by 3.12 percent from 2014. Population density 3,682 inhabitants / km2Conducted to find out the extent of the impact caused by the development and change of land function which is marked by the utilization of land for the activities in the suburbs towards the function of Garuda Sakti street, Tampan Sub-district. The objective of this study is to produce the projection of Garuda Sakti Street function in the next five years, namely in 2022.The changes in residential land, trade and services, education and healt is increasing an average of 17.02 per year. movement of settlement area by 0,0095 smp/hour/m2, trade and service area of 0,0111 smp/hour/m2, education area 0,2603 smp/hour/m2 and health area 0,1738 Smp / hour / m2. The volume of traffic flow at peak hour is 1567 smp/hour. With a capacity of 1866 pcu/hour, the road class is debated into the secondary collector category.The suggestion in this research is that it is needed to improve the management of traffic engineering and consider to raise the road class become the primary collector.Keyword: Regional Development, Land Changes